Influence of Feeding Management and Seasons on Yield and Composition of Milk Produced from Friesian Crossbred Cows Raised Under Hot and Humid Environment in Central Thailand - Sutthisak Kaewkamchan; Pravee Vijchulata; Pornsri Chairatanayuth; Sirinporn Sintuvanich; Vilai Santisopasri; Somjit Surapat (Agriculture and Natural Resources, 2002)
A twelve-month on-farm experiment was carried out to investigate the effects of feeding management and seasons on yield and composition of milk from a total of 825 dairy cows with different Friesian crossbred levels raised under the hot and humid environment in central Thailand. Forty pre-selected farms were classified into two groups of twenty farms each (standard and substandard) according to feed and feeding management practices. The cows in first group received feeds that met the NRC’s energy and protein daily requirments, whereas those in the second group were provided with substandard feeding practices. The % Friesian crossbred cows were classified into < 75, 75, 87.5, and >87.5 %. All cows were raised indoors throughout the three seasons (summer, rainy, and winter). It was observed that milk yield from cows fed the standard diet, averaging 15.90 kg/day, was 2.02 kg/day higher (P<.01) than those in the substandard group. The standard fed cows produced 0.25 % more (P<.01) milk fat (4.37 versus 4.12%), 0.16% milk protein (3.43 versus 3.27%), and 0.23 % SNF (8.81 versus 8.58 %) than the substandard ones respectively. Milk yield increased proportionally with increasing % Friesian crossbred levels, whereas milk components gradually decreased. The decline in milk composition was higher in the substandard fed group when compared to the group receiving the standard feed. In addition, the cows during the hot season produced milk with lower (P<0.01) milk protein and SNF than those in the remaining rainy and winter seasons.